COVID - 19: Introdução e medidas de enfrentamento ao novo coronavírus em Santarém (PA), um município de médio porte da Amazônia brasileira - Silva, Jaqueline Portal da (Universidade Federal do Pará, 2023)
Cities in the Brazilian Amazon have been highly impacted by the new coronavirus pandemic. In Santarém (PA), in the first three months of 2021, the number of deaths from COVID-19 corresponded to 54% of the total deaths in 2020. A year after the first record of the disease, the municipality had 16.734 positive cases and 830 deaths. Therefore, the present research aimed to enunciate the temporal behavior of the new coronavirus in Santarém (PA) between April 1, 2020 and April 1, 2021 regarding morbidity and mortality.This is a study with an interdisciplinary methodological approach, based on data from epidemiological bulletins published by the municipal health department, and also federal, state and municipal decrees on measures to combat the pandemic, as well as recent scientific bibliographic research. The geographic location, the extensive river network, the low adherence of the population to social distancing and the limited availability of hospital beds - especially in intensive care units that can meet the demands of the western region of the state - contribute to the establishment of COVID-19 as a public health problem in the municipality.